The Impact of Service Quality and Brand Image Through Passenger Satisfaction During New Normal Pandemic Covid -19 - Yulianti Keke; Honny Fiva Akira; Abel Abel; Teddy Hardiand; Yuliantini Yuliantini; Abdul Ghafar; Ika Utami Yulihapsari (Majalah Ilmiah Bijak, 2023)
Service quality in a service company is very important and becomes a reference for good or bad companies in serving their customers so that they are able and create customer satisfaction for the company. And a good brand image will produce and the formation of a good reputation for the company within the eyes of consumers will bring client fulfillment. This ponders points to analyze the benefit quality and brand picture on client fulfillment. The data population used in this study were all passengers on the PT. PELNI ship. Where the technique of sampling using the Slovin method which consists of 98 respondents. The data is processed quantitatively by testing the instrument utilizing legitimacy and unwavering quality tests, whereas the information investigation strategy employments numerous direct relapse analysis, coefficient of assurance, t test and f test. The research data processing was carried out using SPSS version 25. The comes about of this think about showed that Benefit Quality and Brand Picture had a positive and significant impact on Passenger Satisfaction with a level of determination of 89.3%, of which 10.7% was influenced by other factors..